Meteorological extremes and their variability on different time scales - Sienz, Frank (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2010)
The analysis of extremes is of increasing importance in meteorological science. This is mainly due to the associated damages caused by the events and the expected changes going along with changing climate conditions. Extremes are of relevance in different fields and can be classified by the time scale of the generating processes. This circumstance complicates the analysis, beside their inherent rareness.These complications have to be overcome with adequate methods and the following are applied: Standardized Precipitation Index (SPI), extreme value statistics and extreme event return time analysis. This study contributes to the description of extreme events. The more technical oriented part discusses shortcomings of the applied methods and resolves them partly.The impact of climate variability and climate change on frequency and intensity of the extremes is analyzed for Icelandic precipitation and North Atlantic cyclones. Further, extreme event return time properties are investigated in long-term memory processes near 1/f.